Stability And Data Dependence Results For The Mann Iteration Schemes on n-Banach Space - Hamed, Mustafa Mohamed; Jamil , Zeana Zaki (Iraqi Journal of Science, 2020)
Let be an n-Banach space, M be a nonempty closed convex subset of , and S:Mâ†’M be a mapping that belongs to the class mapping. The purpose of this paper is to study the stability and data dependence results of a Mann iteration scheme on n-Banach space